Incidence of Plasma Leakage in Dengue Hemorrhagic Fever - Sultana, Humayra; Sultanuddin; Karim, Rashidul; Rahman, Md Shafiqur; Rahat, Sayeda Farzana; Rahman, Mohammed Mahfuzur; Rahman, Md Shakibur; Sharmin, Rummana (Journal of Dhaka National Medical College & Hospital, 2020)
Background: Dengue is still existing as an important threat to child health. This virus induces wide spectrum of clinical conditions including dengue hemorrhagic fever (DHF), characterized by plasma leakage and bleeding, which is often life endangering. Dengue is showing a recent upsurge in Bangladesh when Covid 19 is threating huge number of human lives. Objective: Plasma leakage is the key feature of serious DHF. Early clinical suspicion, establishment of diagnosis of dengue hemorrhagic fever (DHF) or dengue shock syndrome (DSS) and proper therapeutic intervention are crucial for saving lives. This study is undertaken to see the severity nature of Dengue infection in our territory. Methods & Materials: Eighty one admitted children in the Paediatric ward of DNMI H, had been suffering from various dengue infection were included in study. Diagnosis was made by history taking, clinical features and supporting investigative findings like Leukopaenia, Thrombocytopacnia and haematocrit (raised or not), NS1 antigen positivity, Dengue antibodies (IgM & IgG) and Radiological & sonographic evaluation of the Chest and Abdomen. Result: 43 children (53%) were male and 38 (43%) female. The age range was from 06 months to 13 years. Fifty eight (71.60%) were urban and the remaining 23 (28.40%) were from rural areas. Chief complaints were fever with unusual weakness. Temperature recorded were 100F to 103F except in 02 cases in whom fever remitted before admission. Other important symptoms were Headache and rarely Haemorrhagic manifestations. Thrombocytpaenia found in all cases and Leukopaenia in 56 (69.14%) children. Haematocrit were raised (>10%) in 9 patients only. Features of plasma leakage (Pleural effusion/Ascites/Bleeding sign) found in 09 children those have raised haematocrit. Among all children 78 recovered, 03 cases (01 with uncontrolled gastrointestinal hemorrhage and 02 with breathing difficulty demanding ICU support) were referred to better center. Conclusion: Ultrasonographic signs and changes in hematocrits are useful tools for detecting plasma leakage in dengue infection. Pleural effusions and ascites are common features. With careful therapeutic intervention patients improve rapidly but should be monitored closely as leakage may continue for couple of days. J. Dhaka National Med. Coll. Hos. 2020; 26 (02): 10-14